Lipid-lowering effectiveness of a Russian generic of atorvastatin in patients with various hyperlipidaemia phenotypes - P. P. Malyshev; T. A. Rozhkova; Z. Yu. Malmakova; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика)
Aim. To assess lipid-lowering effectiveness of generic atorvastatin in patients with various hyperlipidaemia (HLP) phenotypes in an open, short-term (four weeks) study.Material and methods. All participants were divided into two groups — with isolated hypercholesterolemia (HCH) and normal fasting triglycerides, (n=25), and with combined HLP and TG levels >1,7 mmol/l (n=26). Atorvastain dose was 20 mg/d. Serum levels of total cholesterol (TCH), TG and high-density lipoprotein cholesterol (HDL- CH) were measured by standard enzyme methods. Medication effectiveness was assessed by the reduction in low- density lipoprotein CH (LDL-CH) and TG levels.Results. In both groups, the medication significantly decreased serum levels of LDL-CH by 34-36,4%, without any substantial inter-group difference. However, lipid-lowering effect in patients with lower baseline TG levels was stronger than in individuals with normal TG concentrations — 27,1% and 12,9%, respectively (p=0,027).Conclusion. Cholesterol-lowering effect of generic atorvastatin (20 mg/d) was similar in patients with IIa and IIb HL. The effect on TG levels depended on HLP phenotype and was greater in individuals with higher baseline TG levels.